Bioethanol production from renewable polymer lichenan using lichenase from an alkalothermophilic thermomonospora sp and thermotolerant yeast - Menon, Vishnu; Divate, Rupesh; Rao, Mala (Fuel Processing Technology, 2011)
Biomass feedstocks available decentrally will be more commodious for localized biorefinery approach than the exhaustive large scale and centralized plants driven by cost intensive technology. Lichen is present in a wide range of habitats in a distributed manner. A maximum hydrolysis of 73%-76% for lichenan from Cetraria islandica, Usnea barbata and Parmelia sp. were obtained in 24 h using lichenase from an alkalothermophilic Thermomonospora sp. wherein the hydrolysis was 100% with commercial enzyme Accellerase (TM) 1000. The synergistic role of beta-glucosidase in lichenan hydrolysis was demonstrated by the exogenous addition of beta-glucosidase to Thermomonospora lichenase which resulted in complete hydrolysis. The hydrolysates of lichenan obtained using Accellerase or a cocktail of Thermomonospora lichenase and beta-glucosidase when fermented with free cells of Saccharomyces at 40 degrees C produced an ethanol yield of 0.45 g/g-0.48 g/g with theoretical conversion efficiencies of 93%-96%. The Ca-alginate immobilized yeast cells were reused eight times at 40 degrees C with 100% fermentation efficiency. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ethanol; Hydrolysis; Lichenan; Lichenase; Synergism; Thermotolerant yeast